Kebijakan Pengembangan Kawasan Minapolitan sebagai Potensi Minawisata di Kecamatan Losarang Kabupaten Indramayu - Khoirunnisa, Anis; Hidayat, Moh. Taufik; Permana, Ipik; Aminulloh, Ali; Abdurrazaq, Muhammad Nurkholis; Susiawati, Iis (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The purpose of this study is to determine the implementation of policies in the development of the Minapolitan area as a potential for tourism in Losarang District, Indramayu Regency, the driving and inhibiting factors that occur, as well as the strategies and efforts made. This type of case study research with qualitative methods were obtained through literature and field studies, with data collection techniques through observation, interviews and documentation studies. Data were analyzed using qualitative analysis with three steps, namely data reduction, presentation, and verification. The results of the study show: 1) the implementation of the policy for the development of the minapolitan area as a potential for tourism in Indramayu district is not optimal as seen from the dimensions of policy implementation which have not been fulfilled properly, namely aspects of policy communication, resources, dispositions, and bureaucratic structure; 2) factors that support this policy are potential natural resources and local cultural wealth, and inhibiting factors are problems with the quality of human resources, infrastructure, lack of regional regulations and legal instruments at the technical level of implementation, budget, public awareness, technology and media public information; 3) the efforts made by the local government to include the development of Minawisata in the regional development plan and communicate it to related parties. Minapolitan entrepreneurs are modernizing salt production so that it has a tourism appeal. While the community's efforts are to take real action to organize the area, clean up waste so that it attracts tourists to come to their area.